2017
DOI: 10.1155/2017/1723658
|View full text |Cite
|
Sign up to set email alerts
|

Remotely Exploiting AT Command Attacks on ZigBee Networks

Abstract: Internet of Things networks represent an emerging phenomenon bringing connectivity to common sensors. Due to the limited capabilities and to the sensitive nature of the devices, security assumes a crucial and primary role. In this paper, we report an innovative and extremely dangerous threat targeting IoT networks. The attack is based on Remote AT Commands exploitation, providing a malicious user with the possibility of reconfiguring or disconnecting IoT sensors from the network. We present the proposed attack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Concerning ZigBee attacks, ad-hoc security testing tools are proposed by [60], while [61] introduces the KillerBee framework, able to execute a wide range of attacks against ZigBee networks. Also, [62] introduces an innovative attack to ZigBee sensor devices, exploiting remote AT commands. Concerning the tools proposed in [60], due to hardware limitations, we do not adopted the proposed software for our tests.…”
Section: Internet Of Things Network May Adopt Different Communicatiomentioning
confidence: 99%
“…Concerning ZigBee attacks, ad-hoc security testing tools are proposed by [60], while [61] introduces the KillerBee framework, able to execute a wide range of attacks against ZigBee networks. Also, [62] introduces an innovative attack to ZigBee sensor devices, exploiting remote AT commands. Concerning the tools proposed in [60], due to hardware limitations, we do not adopted the proposed software for our tests.…”
Section: Internet Of Things Network May Adopt Different Communicatiomentioning
confidence: 99%
“…The ZigBee protocol was created with security considerations in mind, but consumer demand for cheap devices with long life expectancy often caused vendors to sacrifice security, which led to poor implementation of the protocol [49]; this, in turn, led to major security issues such as data compromising or information sniffing. [41]. For example, Vaccari et al [41] focused on the security aspects of the ZigBee protocol.…”
Section: Short Range Communication Protocolsmentioning
confidence: 99%
“…[41]. For example, Vaccari et al [41] focused on the security aspects of the ZigBee protocol. The study identified important security issues and presented an attack on the protocol which enabled the attacker to compromise the data transferring in the network.…”
Section: Short Range Communication Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unmanaged devices have been the cause of well known attacks [27] and its security vulnerabilities are being unceasingly disclosed [28]. The IoT devices are exposing vulnerabilities from the network stack to the software stack [29]. A dysfunctional device can cause the failure of a whole IoT-based system.…”
mentioning
confidence: 99%